Finance and Development, June 1984. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1984)
The role of the World Bank in a changing financial environment is discussed. The World Bank has made several notable changes in its financial structure and operations to assure its continuing financial strength in changing circumstances. Both the front-end fee and the variable lending rate system permit the Bank to pass through to borrowers the consequences of adverse interest rate movements. The Bank's new financial policy has significantly increased its flexibility and reduced its vulnerability to financial turbulence.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet